Measurement and Analysis of Deformation Field Near the Tip of Mode-I Crack in Styrene-Butadiene Rubber - Liu, Huan; Tan, Xiaohua (International Journal of Mechanical and Electrical Engineering, 2025)
To study fracture mechanics in elastomeric materials, digital image correlation (DIC) was used to characterize the deformation field near the crack tip in industrial styrene-butadiene rubber. The sectoral distribution and strain singularity near the crack tip were systematically examined under different loading levels. Experimental results indicated that the crack-tip region was divided into an Expansion Sector (EX) and two Shrinking Sectors (SH). The EX angle increased with the applied load and eventually converged to approximately . Moreover, the strain field near the crack tip demonstrated singular behavior, characterized by three distinct layers: a nonlinear singular layer, an exponential singular layer, and a linear elastic layer. The singularity exponent of the exponential layer remained constant under increasing load, suggesting that the applied load amplified the strain magnitude without changing the intrinsic singularity behavior. These results validate the applicability of the fan-shaped sectoring theory for analyzing large-deformation fracture in styrene-butadiene rubber.